A SEMIOTIC ANALYSIS OF ALADDIN MOVIE BY USING ROLAND BARTHES THEORY - Ayu Famila Putri; Arin Inayah; Wageyono (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2022)
Movie is a picture or life event that is brought to the screen as a means of communication and entertainment. Messages or signs contained in the movie can be analyzed using semiotics. Semiotics is the study of signs. The aims of this research is to determine the types and meanings in semiotics by using Roland Barthes Theory. Roland Barthes developed the theory of semiotics into three stages, namely, denotation, connotation and myth. This research uses descriptive qualitative method. The data taken from scenes and script of Aladdin movie 2019. The researcher collect data by watching movie, observe main characters in scene and movie script, make take note and categorize sentence of semiotics by Roland Barthes theory and analyzes the results data. The types of signs found are denotation, connotation and myth. The researcher found 38 types and meanings of semiotics by Roland Barthes consisting of 21 types and meanings of denotation, 13 types and meanings of connotation and 4 types and meanings of myth. From the explanation above, the types and meanings of denotation is more dominant and the least is myth. The results of this study state that the type of semiotics by Roland Barthes can be used to explain the meaning of semiotics contained in it. The type of Semiotics by Roland Barthes in this movie also has different meanings in describing something according to the reference to the word or phrase used in the movie scene.